Inclusivity Strategy: Swot Analysis For Disabled-Friendly Batik Solo Trans (BST) Shelter - Nur Diansari, Brillian; Prio Agus Santoso, Aris; Fauzan, Fahar; Syariel Ali, Fadlan (LPPM Universitas Duta Bangsa Surakarta, 2024)
Batik Solo Trans (BST) is completed with shelter to increase passenger mobility, but it hasn’t able to attract people of Surakarta for using public transportation. BST shelter was obtained that the ramp was steep, narrow space for wheelchair users and there were no loudspeakers. It can be seen that the BST shelter is not disabled-friendly and must be analyzed for continuous improvement to become a disabled-friendly shelter. This study aims to analyze the Strengths, Weaknesses, Opportunities and Threats (SWOT) of disabled-friendly BST shelter. Inclusive BST shelters are a vital component of a public transportation system that supports mobility for all levels of society including people with disabilities. Competitive strategies that can be implemented to make a disabled-friendly BST shelter are grouped into innovation strategies, socialization strategies and development strategies. By implementing these strategies, the designed BST shelter will be sustainable and disabled-friendly. It can be concluded that public transportation with comfortable, safe, affordable and disabled-friendly is a must for all user needs.